أهميّة تعليم المستوى المفرداتي في مشاريع عبد الرحمن الحاج صالح التطبيقية: المعاجم والذّخيرة أنموذجا: The Importance of Teaching the Lexical Level in Abdel Rahman Al-Hadj Saleh’s Applied Projects: Lexicons and Corpus as a model - Guessoum , Abdul Ali; souilah, Hichem (Maalim, 2024)
The research "The Importance of Teaching the Lexical Level in Abdel Rahman Al-Haj Saleh's Applied Projects: Lexicons and Corpus as a Model.”aims to review the most prominent vocabulary teaching projects by Abdel Rahman El-Hadj Saleh and their significance. This is illustrated through two important linguistic projects: the first is the "Functional Linguistic Repertoire”or the "School Dictionary for the Arab Child,”which seeks to establish a list of diverse vocabulary suitable for the level and needs of learners during their educational stages. The second is the "Arabic Linguistic Corpus Project, ”considered an informative bank of authentic texts that can be used to teach Arabic at all levels. One of the key findings of this research is that the ideas and projects introduced by Abdel Rahman El-Hadj Saleh will significantly contribute, if utilized correctly, to improving the proficiency of Arabic learners throughout their learning journey, and to promoting the Arabic language and expanding its use.